NEW GUIDELINES FOR THE APPLICATION OF INTERNATIONAL ACCOUNTING AND REPORTING STANDARDS AFTER BREXIT - SHKULIPA, Liudmyla (Journal of European Economy, 2023)
The UK’s exit from the EU is currently being studied not only as a major change in geopolitics, but also as a precursor to economic factors that create many accounting and taxation issues between Dublin, London and Brussels. The paper aims to review, identify and predict new guidelines for the application of International Financial Reporting Standards (IFRS) after the UK’s exit from the EU. Three possible benchmarks for the development of British accounting and auditing system after Brexit are identified. The article makes a significant contribution to the research by analytically assessing the UK’s accounting regulations after its exit from the EU, and comparing the functions of the new financial accounting board in London with those of the previous board. The study helps to define the guidelines for the further application of accounting standards in the UK and to highlight the prospects for the development and application of IFRS, both in the short and long term. For Ukraine, at a time of potential accession to the EU in 2024-2025, these issues are also relevant, as the UK, in addition to the EU, has become a significant economic partner for Ukraine during the war. JEL: M48, K22, G15, G17